ASSESSMENT SYSTEM, TAX RATES AND TAXPAYER AWARENESS OF UMKKM TAXPAYER COMPLIANCE IN YOGYAKARTA SPECIAL REGION - Savitri, Wulan Yhanu; Marsuking, Marsuking (IJMA (Indonesian Journal of Management and Accounting), 2021)
Taxes are a source of state revenue. Taxes can be said to be a support in national development. One of the tax contributors in Indonesia is MSMEs. MSMEs are a dominating business in Indonesia. Currently, the number of MSMEs in Indonesia is around 64.2 million MSMEs spread throughout Indonesia. However, the growth of MSMEs is not accompanied by the compliance of MSME taxpayers. This research aims to determine the influence of tax sanctions, the implementation of self-assessment systems, tax rates and awareness of MSME taxpayers in the Special Region of Yogyakarta.This type of research is quantitative research. The research population is MSMEs located in DIY, sampling by Random Sampling method. Data processing using IBM SPSS application version 2. with descriptive analysis and multiple linear regressions.The results show that partially tax has no effect on taxpayer compliance, the Self Assesment System has a positive effect on taxpayer compliance, tariffs have no effect on taxpayer compliance and taxpayer awareness has an effect on taxpayer compliance. Simultaneously tax sanctions, self-assessment system, tax rates and taxpayers have an effect on MSME taxpayer compliance.